The effect of Gang Angle of Offset Disc Harrows on Soil Tilth, Work Rate and Fuel Consumption - Serrano, João M. (2012)
In offset disc harrows, the angle between gangs may be changed to meet the field conditions. Tractor drivers usually use an angle close to maximum, increasing power requirements and therefore limiting the forward speed and, consequently, the work rate. The objective of this work was to study, in the specific soil conditions present in Southern Portuguese agriculture, the effect of working with a disc harrow at a reduced gang angle and at a higher forward speed, in terms of work rate, fuel consumption per hectare and distribution of dry soil aggregates. A trailed type medium-weight offset disc harrow (20 discs of 610mm diameter) was used, pulled by a four wheel drive tractor. A portable computer based record system was used to collect engine speed, actual forward speed, slip, fuel consumption and draught force. Higher work rates and lower values of fuel consumption per hectare were attained, with no visible difference in soil tilth, by operating the disc harrow at a lower angle between disc gangs and shifting up to a higher gear ratio whilst maintaining engine speed. Tractor drivers, particularly those with tractors equipped with performance monitors should consider setting, by preliminary tests prior to the main field work, the right combination of gang angle and forward speed within the limits of quality of the work and the safety of the operation.